2019
DOI: 10.3390/su11174739
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Using POI and Nighttime Light Data to Map Urban Road Safety at the Micro-Level: A Case in Shanghai, China

Abstract: The way in which the occurrence of urban traffic collisions can be conveniently and precisely predicted plays an important role in traffic safety management, which can help ensure urban sustainability. Point of interest (POI) and nighttime light (NTL) data have always been used for characterizing human activities and built environments. By using a district of Shanghai as the study area, this research employed the two types of urban sensing data to map vehicle-pedestrian and vehicle-vehicle collision risks at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Density index is an index reflecting the intensity of land and space development, which has been used to guide urban spatial planning [43] and sustainable development of urban ecosystem [66,67]. In this study, the density index is the ratio of the production space area of the manufacturing industry to the total area of the urban built-up area, which reflects the development intensity of the manufacturing production space.…”
Section: Density Indexmentioning
confidence: 99%
See 3 more Smart Citations
“…Density index is an index reflecting the intensity of land and space development, which has been used to guide urban spatial planning [43] and sustainable development of urban ecosystem [66,67]. In this study, the density index is the ratio of the production space area of the manufacturing industry to the total area of the urban built-up area, which reflects the development intensity of the manufacturing production space.…”
Section: Density Indexmentioning
confidence: 99%
“…The formation of the spatial pattern of manufacturing production space was the result of the combined effects of multiple factors. Using for reference of scholars' research on manufacturing space reconstruction and the study of its influencing factors [31,70], the quantitative research on industrial production spatial characteristics [43,44] combines with the industry characteristics of the PRD manufacturing industry [17], in this study the analysis framework shown in the Figure 4 was constructed. Furthermore, taking 37 counties (districts) in the PRD as statistical units, the leading factors affecting the spatial pattern of manufacturing production space in the PRD were analyzed by constructing regression model.…”
Section: Regression Model Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…The former describes the characteristics of the built environment on the roads such as crossings, traffic lights, sidewalks, and roadside trees that may influence the behavior of the elderly while walking, and the latter is used to delineate features of the community such as bus stops, supermarkets, shopping centers, and clinics that probably affect the daily activities of older people. Despite the limited research on the influence of the built environment on older pedestrians, many studies have focused on the effects of environmental factors on pedestrians of all ages [ 24 , 25 , 26 , 27 ]. This research selected variables by referring to previous studies on pedestrians regardless of age.…”
Section: Study Area and Datamentioning
confidence: 99%